Socio-spatial synthesis as a methodological tool for evaluating the urban environment - Tajour Majd (Архитектон)
The article justifies the need to update methods for analyzing the urban environment. Current methods are characterized by fragmentation and a lack of comprehensiveness in assessing the current urban situation. The purpose of this study is to develop a new methodological tool for evaluating the urban environment, called by the author "social-spatial synthesis," which would allow the integration of known analytical methods. The theoretical foundations of the "social-spatial synthesis" concept are presented as a tool for integrative analysis and systematically evaluating open public urban spaces. The proposed environmental approach involves the integration of morphological, sociological, and phenomenological spatial methods of analysis and, consequently, provides an opportunity for an objective identification of real problems in the urban environment and the formulation of tasks for its improvement.